The Influence of Spiritual Factors on Business Survival of Asnaf Entrepreneurs in Malaysia - Ali, Nor Aini; Sarif, Suhaili; Kamri, Nor `Azzah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The Covid-19 pandemic and the enforcement of the Movement Control Order (MCO) in Malaysia adversely affected many entrepreneurs including business owners who received zakat assistance. Amidst the challenges, many of them managed to survive and remained strongly motivated. This article hence aims to analyze the spiritual factors that help asnaf entrepreneurs (eligible zakat recipients) during the Covid-19 pandemic to remain in business. A qualitative study was used in this research by interviewing a total of 46 asnaf entrepreneurs from three zakat institutions. The respondents were selected via purposive and snowball sampling methods. The findings of the study show that spiritual factors such as iman, amanah, perseverance, tawakkal and ihsan have significantly influenced the morale and development of asnaf entrepreneurs. Therefore, it is suggested that zakat institutions should not provide their recipients with merely financial assistance, but also non-material spiritual enhancement support such as motivational courses and advisory. Such programs will help asnaf entrepreneurs to uplift their spirit, especially during challenging times.